Study on Management Scheme about Intelligent Construction of Long-distance Water Diversion Project - XIAO Bin (Renmin Zhujiang)
The construction of a long-distance water diversion project has the characteristics of multiple points,a long distance,many participating units and a complex construction environment.With the rise and integrated application of a new generation of information technology,it is often faced with problems such as different understandings of digital technology,non-standard management,imperfect system and no clue in its intelligent construction.Combined with the improvement of the digital work including organizational structure,division of responsibilities,specific implementation process of BIM+GIS and management system of achievements for the water resources allocation project in the Pearl River Delta,relevant experience can be summarized for the management of intelligent construction of other long-distance water diversion projects,and a digital solution will also be created for each project with its engineering characteristics.